KOMUNIKASI INSTRUKSIONAL PENGASUH DALAM PROSES BELAJARA MENGAJAR PADA PROGRAM TAHFIDZ QUR’AN DI PONDOK PESANTREN UMAR BIN KHATAB PEKANBARU - Rafi Syas Gapita; Nova Yohana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Qur'an tahfidz program in Umar Bin Khatab School is superior program of Salafiyah Ula grade of student that spends 75% hours from all study schedule in a week. It is not simple for teaching material to be memorized for children, especially in elementary grade. This condition causes teacher to use instructional communication method for teaching student. The purpose of this research should be to know adviser capability in this school, to know what kind of adviser's method and also to know communication obstacle in learning process.The research uses qualitative research method that is completed by descriptive analysis. All informant is adviser as if teacher, and also all choosing student that was decided by purposive method of sampling. Data Collection can be found by observation, interview and documentation. Data Validation comes from participative extension amd triangulation.The result of this research shows communicator credibility has been good that is viewed by teacher's memorizing skill of Qur'an and teaching Qur'an tahfidz to student and their trust to the teacher. There are many various of instructional communication methods such as givin demonstration, practising with friends and giving some tasks. Beside that, there are two obstacles should be faced, technical and psychological obstacle. Technical obstacle can be found in handling class condition of noisy because of unbalancing the number of both teacher and student. It causes teacher getting out of monitoring. Then, psychological obstacle can be seen from different capability of memorizing between students and also student often forgets half of their memories instead.Keyword: Instructional Communication, Learning Process, Qur'an Tahfidz